PANDANGAN FILSAFAT TERHADAP PENDIDIKAN KARAKTER SECARA ONTOLOGI, EPISTIMOLGI, DAN AKSIOLOGI (STUDI LITERATUR) - Ricky Gustiawan; Yeni Erita; Desyandri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
Character education is a conscious and planned human effort aimed at educating and empowering every potential student. Apart from that, character education is also useful for building the character of each individual so that they can become individuals who can have benefits for these individuals and also the surrounding environment. This study examines and describes how the theoretical basis for character education is conceptualized and how the theoretical basis for character education is implemented. The theoretical basis of character education includes the basis of ontology, the basis of epistemology and the basis of axiology. In this case the researcher can explain how to conceptualize and implement the ontology, epistemology and axiology of character education.